Design, Greenhouse Emissions, and Environmental Payback of a Photovoltaic Solar Energy System - Herwin Saito Schultz; Monica Carvalho (Energies, 2022)
This study aims to design a 16.4 MW photovoltaic solar system located in the Brazilian Northeast and quantify the associated greenhouse gas emissions and environmental payback. The energy system was designed to minimize the Levelized Cost of Energy. The greenhouse gas emissions were quantified with the Life Cycle Assessment methodology, expressing the environmental impact in terms of generated energy (kg CO2-eq/kWh) and following ISO 14040 and 14044. The environmental payback considered the Brazilian electricity mix and degradation of the panels. The results indicated a system capable of producing 521,443 MWh in 25 years, with an emission factor of 0.044 kg CO2-eq/kWh and environmental payback of five years and eight months. The emission factor is at least ten times lower than thermoelectric natural gas power plants. The solar panels were the main contributors to the greenhouse gas emissions, representing 90.59% of overall emissions. It is concluded that photovoltaic energy systems are crucial in the search for emissions mitigation, even in a country that presents a predominantly renewable electricity matrix, with demonstrated environmental benefits.